Nilai Dakwah dalam Parno Adat Turun Mandi di Desa Mukai Mudik Kecamatan Siulak Mukai - Moni Novita Sari; Jalwis Jalwis; Ivan Sunata (Institut Agama Islam Negeri Kerinci, 2023)
The purposed of this reasech was to analyzed the worth of da'wah in the customary parno of bathing children at Mukai Mudik Village, a tradition that has been ingrained in the society. Al-Qur'an and Sunnah are guidelines in our life, we should continue to hold on to these two guidelines so that we are always on the right path and pleased by Allah SWT. The method used in this research was a qualitative descriptive approach. Where the data was obtained from observation, interviews and documentation. The data was analyzed by reviewing, and compiling data in the units that can be managed from the field that are considered meaningful to researcher and become a result of what was founded. The results of this research proved that there were Islamic values in the form of faith, sharia and morals in the customary parno of bathing children in the Mukai Mudik village, with an element of da'wah in customary parn. This customary parno should be preserved as a tradition from predecessors for the next generation.